E-learning technologies at the secondary education level: literature review - Cardona-Acevedo, Sebastián; Agudelo-Ceballos, Erica; Cumpa Vásquez, Jorge Tomás; Martínez Rojas, Ezequiel; Valencia-Arias, Alejandro; Jimenez Garcia, Jesus Alberto; Benjumea-Arias, Martha Luz (Frontiers in Education, 2025)
IntroductionE-Learning Technologies play an integral role in secondary education, providing flexible and personalized learning environments through online platforms, mobile applications, and interactive resources. These tools have transformed access to knowledge and participation in the educational process, promoting autonomy and self-directed learning. However, significant gaps in research remain, underscoring the necessity for bibliometric analysis to address these gaps. The objective is to examine the current research trends on this topic.MethodsA bibliometric analysis was conducted in accordance with the PRISMA-2020 guidelines, using the Scopus and Web of Science databases.ResultsThe results demonstrate that the years of greatest interest are 2022 and 2021, with a notable increase in the number of publications. The principal references include the work of Hwang and the journal Sage Open. Thematic evolution has progressed from virtual environments to encompass a range of subjects, including the Coronavirus (COVID-19), physical education, training, and motivation. The primary cluster encompasses terms such as “Intellectual Disability” and “Students.” The most prevalent keywords are related to the ongoing pandemic, including “COVID-19,” “motivation,” and “physical education.”DiscussionAdditionally, the emergence of new concepts such as “communication” and “effectiveness” is noteworthy. These trends underscore the necessity for a research agenda that prioritizes a more profound examination of these pivotal topics and the rectification of existing deficiencies in the existing literature.